Exposição à baixa concentração de chumbo reduz a força cardíaca em músculos papilares isolados de ratos - Silva, Marito Afonso Sousa Costa (2014)
Chronic lead exposure produces hypertension, but its effects at low concentrations on cardiac function are still poorly understood. We aimed to investigate whether low plasma concentrations of lead can modify cardiac contractility in isolated papillary muscles of rats. Wistar rats were divided into two groups: control (TC) and treated with lead (Pb2 +) (100 ppm in drinking water for 15 days). Blood pressure was measured at time zero and at the end of 15 days. At the end of treatment, animals were anesthetized and euthanized, and the parameters of contractility of isolated papillary muscles was recorded. The Pb2+ rats had blood lead concentration of 12,3 µg/dL. The animals' blood pressure Pb2+ raised at the end of treatment. In vitro, treatment with lead did not alter the force and its time derivatives, but decreased the activation time and relaxation. Furthermore, the inotropic response induced increase of calcium extracellular (Ca2+ ) was reduced in the group Pb2+ . These results suggest changes in calcium kinetics in cardiomyocytes of rats exposed to lead. However, the uptake of Ca2+ by the sarcoplasmic reticulum and protein expression of SERCA and fosfolamabam were not modified. To evaluate, in vitro, the involvement of L-type Ca2+ using blocker verapamil reduction in the strength was observed in both experimental groups. These findings suggest that the reduction of the inotropic response to Ca2+ does not appear be related to changes in flow transarcolemal this ion, but suggests a possible change in contractile proteins. Our results show that even at concentrations below the levels recommended as safe, lead cause deleterious effects on the contractile machinery of the heart and should be considered as a risk factor for development of cardiovascular disease.